Biomedical knowledge, clinical cognition and diagnostic justification: a structural equation model. Issue 3 (8th February 2013) - Cianciolo, Anna T; Williams, Reed G; Klamen, Debra L; Roberts, Nicole K
<x xml:space="preserve">Abstract</x> Context The process whereby medical students employ integrated analytic and non‐analytic diagnostic strategies is not fully understood. Analysing academic performance data could provide a perspective complementary to that of laboratory experiments when investigating the nature of diagnostic strategy. This study examined the performance data of medical students in an integrated curriculum to determine the relative contributions of biomedical knowledge and clinical pattern recognition to diagnostic strategy. Methods Structural equation modelling was used to examine the relationship between biomedical knowledge and clinical cognition (clinical information gathering and interpretation) assessed in Years 1 and 2 of medical school and their relative contributions to diagnostic justification assessed at the beginning of Year 4. Modelling was applied to the academic performance data of 133 medical students who received their md degrees in 2011 and 2012. Results The model satisfactorily fit the data. The correlation between biomedical knowledge and clinical cognition was low–moderate (0.26). The paths between these two constructs and diagnostic justification were moderate and slightly favoured biomedical knowledge (0.47 and 0.40 for biomedical knowledge and clinical cognition, respectively). Conclusions The findings suggest that within the first 2 years of medical school, students possessed separate, but complementary, cognitive tools, comprising biomedical knowledge and clinical pattern recognition, which contributed to an integrated diagnostic strategy at the beginning of Year 4. Assessing diagnostic justification, which requires students to make their thinking explicit, may promote the integration of analytic and non‐analytic processing into diagnostic strategy.